Reflexive Identity Construction in South Asian American Diaspora in Jhumpa Lahiri’s The Namesake - Muqarram Khorakiwala (Universidad de Valladolid, 2021)
Cultural identity in contemporary diasporic communities is dynamic, multifaceted, and cyclical. In the age of reflexive modernity, it is imperative to think about new ways of conceptualizing the experience of individuals straddling multiple geographies. A model of identity for such individuals should not only explain the plurality of “being” but also the fluidity of “becoming.” In this article, the question of multiple and shifting identities of the four main characters in Jhumpa Lahiri’s intergenerational novel, The Namesake, is explored using an interdisciplinary model from the field of business management based on Giddens’ theorization of reflexivity. The inward reflexive relationship between the “self” and the “other” through the discursive articulation of the ontological journey of the novel’s characters highlights the complex nature of diasporic identity construction.